PRODEO DALAM PERADILAN SEMA NOMOR 10 TAHUN 2010 - Angkasa, Nawa (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2016)
The parties who could not afford, can file a lawsuit/petition in prodeo. The State can't afford it should be proved by certificate of the head of the concerned villages. In the register matter it will be recorded. All receipts and expenditure, though none in the journal must remain recorded. Before a lawsuit is recorded in the register book, plaintiff in advance are to apply for litigants in prodeo, which if granted, the Judge makes the determination about the permit litigants in prodeo, after previously opposing parties are given the opportunity to respond to the petition. About granting permission beracara in prodeo applies to each level of the judiciary in own-¬ itself and can not be given to all levels of the judiciary. Defendant who cannot afford to pay the fees, are also eligible to apply in such a way the prodeo above. The petition against the litigants in prodeo, the judge makes the determination of diizinkannya beracara in prodeo after previously opposing parties are given the opportunity to determine ¬ patan to respond (in accordance with article 237, and HIR Article 273 RBg).